Preoperative neoadjuvant chemoradiotherapy provides borderline resectable thoracic esophageal cancer with equivalent treatment results as clinically T3 thoracic esophageal cancer - Akiyuki Wakita; Satoru Motoyama; Yusuke Sato; Yushi Nagaki; Hiromu Fujita; Kohei Kemuriyama; Kenjiro Hayashi; Kazuhiro Imai; Hiroshi Nanjo; Yoshihiro Minamiya (Annals of Gastroenterological Surgery, 2023)
Abstract Aim Because the optimal treatment strategy for borderline resectable (cT3br) thoracic esophageal cancer patients remains unclear, it is of great interest whether preoperative neoadjuvant therapy for cT3br could achieve results comparable to those seen with resectable T3 cancer (cT3r). We speculated that preoperative neoadjuvant chemoradiotherapy (NACRT) would be particularly effective in cT3br thoracic esophageal cancer patients and compared to cT3br and cT3r. Methods Of 186 cT3 thoracic esophageal cancer patients treated with intended NACRT, 162 received radical esophagectomy. More than 97% were squamous cell carcinomas. Patients were partitioned into two groups according to whether invasion of adjacent organs was suspected (cT3br and cT3r). Treatment outcomes and survival were analyzed. Results Sixty‐eight patients (36.6%) were classified as cT3br and 118 (63.4%) as cT3r. The cT3br group had significantly more tumors in the upper and middle mediastinum (p < 0.0001) and more cases with cM1 (lymph node) (p = 0.0104) than the cT3r group. In addition, the cT3br patients receiving esophagectomy exhibited a significantly lower pathological complete response rate than the cT3r patients (p = 0.0374). However, the R0 resection rate did not differ between the cT3br and cT3r patients (p = 0.0978), and the two groups treated with intended NACRT had similar 5‐year overall (OS) and disease‐specific survival (DSS) (p = 0.3831 and p = 0.9020). In addition, the incidence and patterns of recurrence did not differ between the cT3br and cT3r patients receiving esophagectomy (p = 0.8109 and p = 0.3128). Conclusions Preoperative neoadjuvant chemoradiotherapy appears to be a promising treatment for patients with borderline resectable thoracic esophageal squamous cell carcinoma.